ANÁLISE DOS ÍNDICES FÍSICOS DA CINZA DE RESÍDUOS SÓLIDOS URBANOS E DA AREIA NATURAL - Cechin, Luana; Consul, Marcio; Martins, Mariane; Graupmann, Olaf (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this study is to analyze the contents of the physical medium sand and ash from municipal solid waste resulting from heat treatment processes. Assays were performed in the laboratory to characterize the physical indexes from sand and ash, the tests used were water absorption, dry bulk density of the aggregate density by the pycnometer, specific gravity bottle of Chapman and the material passing through the sieve 0.075mm. The importance of this study is due to the fact that the ash is a material resulting from the burning of solid waste for landfill which generates an environmental liabilities, and may cause damage to the environment. However, the use of this material can reduce the impact on the environment.